The fabrication of antibacterial hydrogels for wound healing - Zhang, Xiumei; Qin, Miao; Xu, Mengjie; Miao, Fenyan; Merzougui, Chaima; Zhang, Xiangyu; Wei, Yan; Chen, Weiyi; Huang, Di (European polymer journal, 2021)
[Display omitted] Antimicrobial hydrogels have been proposed to be interesting materials used for wound healing due to their unique properties. Therefore, numerous scientists have made efforts to design and synthesize antibacterial hydrogels. At present, there are two commonly used methods for preparing antibacterial hydrogels. One is combining antibacterial agents with hydrogels. Antibacterial drugs include antibiotics, some biological extracts, natural polymers and some metal nanoparticles. In this review, physical combination (directly incorporating, swelling diffusion method, encapsulated in carriers) and chemical combination (hydrogels with inherent antibacterial activity, forming chemical bonds) are introduced depending on the methods and types of antibacterial agents incorporated with hydrogels. The other one is light-assisted antibacterial hydrogels, which involve photo-thermal antibacterial hydrogels and photo-dynamic antibacterial hydrogels. The common methods to prepare light-assisted antibacterial hydrogels are also described in this work. With the rapid improvements in antibacterial technology, many novel antibacterial hydrogels are constantly emerging. The most relevant studies and the latest status of research in this area were evaluated in this review.